Effect of grain size distribution on the shear properties of sand - Guo, Hong; Wang, Shaofei; Guo, Chen; Yang, Kuibin; Guo, Rui; Fu, Jiangtao; Nan, Yalin; Tao, Mingjiang (Frontiers in Materials, 2023)
In this study, we investigated the effect of particle size distribution on the shear properties of sand. Direct shear tests were conducted using four types of sand samples with different particle size distributions obtained from standard sand produced by Xiamen ISO Co. Ltd. The results show that the influence of particle size distribution on the internal friction angle was significant.Typically, the internal friction angle increases with increasing the coefficient of non-uniformity (Cu) and decreasing the curvature coefficient (Cc). The discrete element results show that the initial particle size distribution significantly affects the porosity, coordination number, and particle slide fraction. In addition, the grey relation analysis revealed that the sliding fraction and coordination number have the greatest correlation with the internal friction angle. The research results of this study help to understand the changes in particle contact, internal stress, and particle sliding during the shear failure process of sand.